(untitled) (Global Journal of Human-Social Science, 2023)
Reading is one of the elements que compose the setting of socio-spatial practices of young people in the metropolis However the forms and objects of reading Have Been Transformed throughout history Thus we propose to problematizes and discuss the place of the youth in the metropolis and how the dynamics of this space can Contribute to the emergence of reading practices For this we start with a bibliographical documentary and exploratory research In the bibliographic research we seek theoretical foundation on the concept of youth place and metropolis In documentary research based on the results of the study Portraits of Reading in Brazil in 2016 we sought to analyze the relationship between the results of the research with the socio-spatial dynamics of the metropolis and how the young man inserts himself in this context Finally some assumptions have Been established for example the socio-spatial dynamics of the metropolis interferons with the formation of the young reader However it is Necessary to mature other questions what is the place of the young man in the metropolis What are the practices reading carried Out By him